Passagens e novas fronteiras dos abates: o Matadouro Municipal de Ponta Grossa e a historicidade dos espaços de matança animal centralizada - Rocha, Lucas Vinicius Erichsen da (2015)
Still lacking specific studies in the Human Sciences, the history of the slaughterhouses integrates the analysis of a production chain from the breeding, their transport, death, industrialization, to the sale and consumption of meat. This human consumption of meat is historically linked to the questioning of how the human species is related not only with other animal species, but also with the spaces where they live and on the constitution of their cultures. For the most part of the of the 19th century, the killing of animals for human consumption was performed without fiscalization and in a way that today we might call precarious. It is during that period that concerns regarding racionalization and modernization of the urban environments are emerging. Increasing government intervention in the social dynamics involved the review of several aspects that concerned the different meat production of moments such as: the condition of creation and death of cattle, new demands about the hygiene of the slaughterhouses, need for centralization, municipalization and inspection of the slaughters; the disciplining of the butchers; and the gradual displacement of the slaughterhouses away from the urban space and vision of the population leading to progressive fading of ethical concerns about the animal death. To build a work to analyse this process of transformations of slaughterhouses and the historicity of animal death for human consumption, it was built a narrative around the specific case of the city of Ponta Grossa/PR. Thus, an investigation was carried in documents that deal with the subject, like minutes of the city council, newspaper excerpts, official publication of the city, posture codes and period images. The public debate surrounding the construction of the municipal slaughterhouse in 1888 and its subsequent shift to the city outskirts in the mid-1930 are examples of a broader movement of the control about the food supplies in urban contexts. Therefore, we seek with this work not only contribute to building a possible history of the slaughterhouses and the historicity of its process, but also increase a historiographical discussion of a practice that directly involves the interface between human societies and nature, ie the meat consumption.